Banking Regulation and Systemic Risk - Martin Summer (Oesterreichische Nationalbank (OeNB), 2002)
The term Systemic Risk belongs to the standard rhetoric of economic policy discussions related to the banking industry. Besides of the goal of protecting small depositors control of systemic risk is given as one of the main arguments for banking regulation. Various recent financial crises have increasingly focussed the regulatory debate on issues of systemic risk and financial stability. In this paper, however, we argue that there is no generally accepted definition of systemic risk and the effectiveness and the economic consequences of various instruments of banking regulation that are intended to attenuate it are still only partially understood both theoretically and empirically. Furthermore we discuss some of the issues raised in this debate by reviewing recent contributions to the academic literature.
Keywords: G21; K23; L51; E58; 330; Banking Regulation; Systemic Risk; Banking Crises